Relationship between wheat flour's quality characteristics and color of fresh wet noodles. Issue 1 (31st December 2023) - Wen, Yaqing; Lin, Shunshun; Li, Xuejie; Zhang, Jian; Zhao, Yang; Ma, Dongyun; Li, Mengqin; Ren, Xiujuan; Zhang, Weifeng
ABSTRACT: Thirty-four wheat cultivars were used to study the relationship between wheat flour quality and fresh wet noodle (FWN) color when stored at room temperature (25°C) over a 24 h period by the partial least squares regression (PLSR) method. Results showed that quality characteristics of wheat flour and their coefficients of variation differed greatly, and the samples were very representative. During FWN storage, the a * value varied greatly, the L * value decreased, and the b * value increased. The results of the correlation analysis showed that the color of wheat flour had significant correlation with FWN ( p <0 .05), and FWN color at 0 h had significant correlation with FWN color changes during 24 h storage ( p <0 .05). Protein, wet gluten, dry gluten, ash content, PPO activity, and water absorption (WA) of wheat flour had significantly negative effects on the L * value of FWN ( p <0 .05). Peak viscosity (PV), trough viscosity (TV), and breakdown viscosity (BV) of the pasting properties of wheat flour contributed greatly to the L * value ( p <0 .05), but had significantly negative effects on the a * value ( p <0 .05). The results showed that quality characteristics of wheat flour profoundly affected FWN color changes during storage, and color, dough strength and pasting properties of wheat flour should be considered comprehensively when selecting the wheat variety for FWN.